2012
DOI: 10.1128/jb.00849-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the P IB -Type ATPases Present in Thermus thermophilus

Abstract: . Mutant strains in which each of the three P-type ATPases was deleted singly were constructed. In each case, the deletion increased the sensitivity of the strain to growth in the presence of copper in the medium, indicating that each of the three can pump copper out of the cells and play a role in copper detoxification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 71 publications
2
20
0
Order By: Relevance
“…We found herein that the expression of ABCB7 was responsible for the reduction of the cadmium concentration from 41 down to 22 nmol per 10 9 cells, making 114 × 10 14 Cd ions pumped by 238 × 10 9 ABCB7 molecules for 3 h yielding 4.4 ± 0.7 Cd ions s −1 molecule −1 . This is in accordance with the ATP hydrolysis activity of metal ATPases such as E. coli ZntA (3.9 ATP/s/molecule; Sharma et al , ), T. thermophilus Zn 2 + /Cd 2 + ‐ATPase (2.4 ATP/s/molecule; Schurig‐Briccio and Gennis, ) and even the human MDR1 (4.9 ATP/s/molecule; Loo et al , ). These results strongly suggest that ABCB3 and ABCB7 are involved in metal detoxification.…”
Section: Discussionsupporting
confidence: 72%
“…We found herein that the expression of ABCB7 was responsible for the reduction of the cadmium concentration from 41 down to 22 nmol per 10 9 cells, making 114 × 10 14 Cd ions pumped by 238 × 10 9 ABCB7 molecules for 3 h yielding 4.4 ± 0.7 Cd ions s −1 molecule −1 . This is in accordance with the ATP hydrolysis activity of metal ATPases such as E. coli ZntA (3.9 ATP/s/molecule; Sharma et al , ), T. thermophilus Zn 2 + /Cd 2 + ‐ATPase (2.4 ATP/s/molecule; Schurig‐Briccio and Gennis, ) and even the human MDR1 (4.9 ATP/s/molecule; Loo et al , ). These results strongly suggest that ABCB3 and ABCB7 are involved in metal detoxification.…”
Section: Discussionsupporting
confidence: 72%
“…CopA and CopB are known to impart copper resistance to S. solfataricus, with CopA being an effective copper pump at low and high copper concentrations, and CopB apparently functioning as a low-affinity copper export ATPase extending resistance at higher concentrations [178]. Similar roles have been observed for the homologous CopA and CopB of Thermus thermophilus, with stimulation of each occurring most in the presence of Cu(I) and Cu(II), respectively [185]. Interestingly, PIB-type copper pumps of the CopA-2 subclass have been implicated in the assembly of metalloproteins, such as the copper-containing cbb3-type respiratory oxygen reductases [186][187][188].…”
Section: Coppermentioning
confidence: 69%
“…Interestingly, PIB-type copper pumps of the CopA-2 subclass have been implicated in the assembly of metalloproteins, such as the copper-containing cbb3-type respiratory oxygen reductases [186][187][188]. As a result, CopA and/or CopB may function together with periplasmic copper chaperons in the assembly of the ba3-type and caa3-type copper-containing respiratory oxygen reductases present in T. thermophilus [185]. However, Völlmecke et al (2012) demonstrated neither PIB-type ATPase, both of the CopA-1 subclass, found in S. solfataricus play an essential role in cytochrome oxidase biosynthesis.…”
Section: Coppermentioning
confidence: 99%
“…5), and the best-characterized enzyme of this subfamily is CopB from A. fulgidus , T. thermophilus , and Enterococcus hirae [8991]. Studies on E. hirae CopB originally suggested that this subfamily was involved in Cu + /Ag + transport [90]; however, it has been shown that although members of this subfamily (specifically A. fulgidus and T. thermophilus CopB) may be partially activated by Cu + and Ag + , tighter binding and higher activity are obtained by Cu 2+ activation, strongly suggesting that this oxidation state of copper is the preferential substrate [90, 91]. Consistent with their role as Cu 2+ transporters, the majority of the P 1B-3 -ATPases have soluble N-terminal extensions that are rich in His residues, and some of these extensions have CXXC motifs (but not ferredoxin-like folds) (Figs.…”
Section: Resultsmentioning
confidence: 99%